Human beta defensin-2 protects the epithelial barrier during methicillin-resistant Staphylococcus aureus infection in chronic rhinosinusitis with nasal polyps - Tengfei Tian; Szuyao Hsu; Qin Sun; Yang Shi; Xianyang Hu; Yang Wu; Keqing Zhao; Chunquan Zheng (Frontiers in Cellular and Infection Microbiology)
ObjectiveWe investigated the effect of human beta defensin-2 (hBD-2) on nasal epithelial barrier function with methicillin-resistant Staphylococcus aureus (MRSA) infection in chronic rhinosinusitis with nasal polyps (CRSwNP).MethodsThe expression of hBD-2 was measured in nasal polyps (NPs) from CRSwNP. MRSA was treated with different concentrations of hBD-2 to assess the invasive ability. Primary human nasal epithelial cells (HNECs) cultured at the air–liquid interface (ALI) were pre-incubated with or without hBD-2 prior to MRSA infection. The cell viability, the epithelial cell integrity, and the tight junction (TJ) expression were evaluated.ResultsThe expression of hBD-2 in the CRSwNP group was higher than that in the control group. In addition, the hBD-2 protein was negatively correlated with the Lund–Mackay CT score and was positively correlated with the neutrophil levels in CRSwNP. The presence of hBD-2 significantly reduced the invasive ability of MRSA in HNECs. MRSA decreased the epithelial cell integrity by diminishing the protein expression of occludin and zonula occludens-1 (ZO-1). Furthermore, hBD-2 prevented the MRSA-induced barrier disruption by increasing the mucosal permeability and the expression of occludin and ZO-1.ConclusionThe results suggest that hBD-2 may partially attenuate the epithelial barrier disruption induced by MRSA, indicating the protective effect of hBD-2 on S. aureus infection.